Creech Hill excavation, Somerset, England. - Unknown:::Creator:::::::::::: (Somerset; England, 2022)
Creech Hill excavation, Somerset, England. In a letter to Elizabeth Otis he writes, "Yesterday afternoon after work, I went up on Creech Hill where some schoolboys are excavating under the direction of the British Museum. A neolithic fort and on top an Iron fort and on top of all a Roman Temple." The important temple site was partially excavated between 1955 and 1960 by Crystal Bennet, an eminent archaeologist based in Bruton.